The impact of green investment, media coverage, and international sales on carbon emission disclosure with audit committee as the moderating variable - Rina Mulyati; Deni Darmawati (Enrichment : Journal of Management, 2023)
This study aims to examine the effect of green investment, media exposure and international sales on disclosure of carbon emissions with the audit committee as a moderating variable. Researchers took data on companies from 2018 to 2021 and used energy company analysis units, basic materials and non-cyclical consumers listed on the Indonesia Stock Exchange. The method of determining the sample in this study is using purposive sampling. The results of this study indicate that green investment has a positive and significant effect on disclosure of carbon emissions, while media exposure and international sales have no significant effect on disclosure of carbon emissions, while the audit committee moderates the effect of green investment and international sales on disclosure of carbon emissions, and the audit committee does not moderate the influence of media exposure on disclosure of carbon emissions.